2019
DOI: 10.25165/j.ijabe.20191202.3058
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental study on eggshell membrane separation device

Abstract: In order to provide theoretical guidance for separating egg membrane from eggshell by using mechanical agitation, CFD was used to explore the flow characteristics in stirred tank, using the Sliding Grid method to deal with the impeller rotational velocity zone in flow field, and using the Euler model to deal with liquid-solid two-phase flow. This study explored the influence of dish-shape bottom or flat-shape bottom, the clearance size between baffle and the side wall, and the axial height of impeller to botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Under optimal conditions, it is expected that all biomethane will be transferred from the solid-liquid reaction to the gaseous phase, ensuring maximum energy recovery. Due to the high difference in density of solid biomass particles, the separation of a solid-liquid mixture is inevitable [3,4] . Specifically, this is manifested as the sedimentation and floating of straw particles, which is not conducive to fermentation [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Under optimal conditions, it is expected that all biomethane will be transferred from the solid-liquid reaction to the gaseous phase, ensuring maximum energy recovery. Due to the high difference in density of solid biomass particles, the separation of a solid-liquid mixture is inevitable [3,4] . Specifically, this is manifested as the sedimentation and floating of straw particles, which is not conducive to fermentation [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Yuji Hasebe ( 31 ) used the difference in specific gravity between eggshell membranes and eggshells to recover batches of eggshell membranes by crushing, ultrasonic irradiation treatment and separation using a sieve, getting a recovery rate of 85–95%. They also designed a cyclone type airflow cleaning device, and the membrane recovery rate was higher than 94% and the membrane cleaning rate was higher than 96% under the optimal operating parameters ( 33 ). Another method is through dissolved air flotation (DAF) invented by using the different solubilities of water under different pressures, and about 96% of the eggshell membrane can be recovered by the DAF separation device ( 41 ).…”
Section: Progress In Research On Eggshell Membrane Separation Technologymentioning
confidence: 99%
“…Acid–alkali methods can be divided into acid, base, and acid–alkali combination methods. Acid ( 33 ) methods can use inorganic acids such as hydrochloric acid and acetic acid because disulfide bonds are more stable under acidic conditions and can be used with reducing reagents such as mercaptopropionic acid to extract eggshell membrane proteins. The alkali method usually uses a strong alkali solution such as NaOH to break disulfide bonds or even peptide bonds to obtain a lower molecular weight protein solution.…”
Section: Advances In Eggshell Membrane Proteolysis Technologymentioning
confidence: 99%
“…The placement angle of the blade has a significant effect on the axial velocity and turbulent kinetic energy in the stirring tank. Through the simulation, it is found that the stirring effect is the best when the blade angle is 45° [8]. A backwater mechanism is designed on the outer wall of the stirring tank.…”
Section: Mixing Mechanism Designmentioning
confidence: 99%
“…According to the test results in Table 2, a response surface regression equation model was established in DesignExpert10.0 software, which takes the distance between the nozzle and plug, the nozzle angle B and the transmission speed C as the independent variable and the uniformity coefficient Y as the objective function. The results are shown in Equation (8). At the same time, the influence of various experimental factors on the uniformity coefficient is obtained by the analysis of variance; the results of the analysis of variance are shown in Table 3.…”
Section: Establishment Of Regression Model and Analysis Of Variancementioning
confidence: 99%